Pengaruh Good Corporate Governance (GCG), Profitabilitas dan Leverage Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI 2018-2022) - Nurul Yuniarti; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of Good Corporate Governance (GCG), profitability and leverage on company value. This research is a quantitative research using secondary data. In this study there were 191 populations where there were only 20 populations that fit the criteria. The sampling method in this study is purposive sampling with judgement sampling type, data collection in this study is carried out with documentation, the technique used in this study is multiple linear regression with the help of SPSS. Based on partial testing, it can be seen that good corporate governance (GCG) does not have a positive and significant effect on company value, while profitability and leverage have a positive and significant effect on company value. Keywords: Good corporate governance (GCG), profitability, leverage, corporate value.